2005
DOI: 10.2337/diacare.28.9.2289
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolic Syndrome: Time for a Critical Appraisal

Abstract: The term "metabolic syndrome" refers to a clustering of specific cardiovascular disease (CVD) risk factors whose underlying pathophysiology is thought to be related to insulin resistance. Since the term is widely used in research and clinical practice, we undertook an extensive review of the literature in relation to the syndrome's definition, underlying pathogenesis, and association with CVD and to the goals and impact of treatment. While there is no question that certain CVD risk factors are prone to cluster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
1,220
5
63

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,008 publications
(1,313 citation statements)
references
References 174 publications
25
1,220
5
63
Order By: Relevance
“…This appears to contribute to disease development in that prior studies indicated that MetS severity confers additional disease risk, even in models that include the individual risk factors,19, 22 contrasting with past perceptions that MetS “was not worth more than the sum of its parts.”35 Also, although MetS severity increases with age, age itself is not a component of the score, as it is with the ASCVD and FRS scores, and the models we tested were not adjusted for age, highlighting the importance of MetS severity for disease risk irrespective of age.…”
Section: Discussionmentioning
confidence: 99%
“…This appears to contribute to disease development in that prior studies indicated that MetS severity confers additional disease risk, even in models that include the individual risk factors,19, 22 contrasting with past perceptions that MetS “was not worth more than the sum of its parts.”35 Also, although MetS severity increases with age, age itself is not a component of the score, as it is with the ASCVD and FRS scores, and the models we tested were not adjusted for age, highlighting the importance of MetS severity for disease risk irrespective of age.…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic utility of the metabolic syndrome construct has previously been called into question 24. Initial studies adjusting for traditional cardiovascular risk factors suggested that the metabolic syndrome construct carries prognostic weight 7, 25, 26.…”
Section: Discussionmentioning
confidence: 99%
“…The intricacies of the debate among official agencies on the clinical importance of MetS [9] are beyond the scope of this article. As a first order approximation, however, we are inclined to follow Reaven's strategy in the Point/Counterpoint paper [10,89] for assessing the need for the concept of MetS.…”
Section: Discussionmentioning
confidence: 99%
“…A subset of these metabolic markers, the TAG:HDL ratio, has been proposed as a simple marker for identifying insulin resistance [8]. It has recently been questioned whether the risk attributed to MetS is greater than the sum of the individual symptoms [9] and, ironically, Reaven has taken the "Con" side on a debate on the viability and diagnostic usefulness of the concept [10,11]. Nonetheless, there seems little controversy on the inherent potential for risk in the individual components.…”
Section: Introductionmentioning
confidence: 99%